Community in 'Global' Academies: The Critical Positioning of 'Meta-Francophone' Caribbeanists. Issue 2 (July 2014) - Gallagher, Mary
<x xml:space="preserve">Abstract</x> Caribbeanists working on the Francophone Caribbean within the Anglophone academy are perhaps particularly well placed to bring into focus the linguistic and cultural losses of the dislocations and relocations of High Capitalism. Although our object of study should facilitate critical insights into the fundamental linguistic and cultural indifference and irresponsibility of capitalist extraction models and into what is at stake politically and ethically in contemporary versions of those profiteering models, the commercialist reductionism currently (re-)formatting not just our own pulverized academic universe, but the entire globe over which it has by now comprehensively spread, surely works against any such truly critical positioning.